PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN GUIDED NOTE TAKING - Utami, Nita Putri; Yulia, Yulia; Ramadona, Serli (Math Educa Journal, 2023)
This study aims to develop lesson plans and handouts based on Guided Note Taking on Algebraic Operations material. This type of research is development research with a 4-D model proposed by S. Thiagarajaan (1974) which consists of four stages of development, namely definition, design, development and dissemination. The define stage consists of: a) educator analysis b) student analysis c) concept analysis d) curriculum/syllabus analysis and learning objectives. The design phase consists of: a) device design b) instrument design and validation of learning device assessment instruments. The develop stage consists of: a) validity stage b) practicality stage. The results of this study indicate that based on the assessment of 5 validators, the learning tool, namely the RPP developed, meets the criteria of being very valid with an average of 90% and the Handout meets the criteria of "very valid" with an average of 88%. Based on the results of filling out practicality questionnaires for educators, student response questionnaires and interviews with students, it shows that the Handout developed is very practical to use in learning mathematics in algebraic operations with an average of 90% by educators and 92% by students. Thus, it can be concluded that this research produces a mathematics learning device based on the Guided Note Taking approach with very valid and practical criteria.